Cystatin C, renal resistance index, and kidney injury molecule-1 are potential early predictors of diabetic kidney disease in children with type 1 diabetes - Trutin, Ivana; Bajic, Zarko; Turudic, Daniel; Cvitkovic-Roic, Andrea; Milosevic, Danko (Frontiers in Pediatrics, 2022)
Background: Diabetic kidney disease (DKD) is the main cause of end-stage renal disease in diabetes mellitus type I (DM-T1) patients. Microalbuminuria and estimated glomerular filtration rate (eGFR) are standard predictors of DKD. However, these predictors have serious weaknesses. Our study aims to analyze cystatin C, renal resistance index, and urinary kidney injury molecule-1 (KIM-1) as predictors of DKD. Methods: We conducted a cross-sectional study in 2019 on a consecutive sample of children and adolescents (10-18 years) diagnosed with DM-T1. The outcome was a risk for DKD estimated using standard predictors: age, urinary albumin, eGFR, serum creatinine, DM-T1 duration, HbA1c, blood pressure, and body mass index (BMI). We conducted the analysis using structural equation modeling. Results: We enrolled 75 children, 36 girls and 39 boys with the median (IQR) age of 14 (11-16) years and median (IQR) duration of DM-T1 6 (4-9) years. The three focal predictors (cystatin C, resistance index and urinary KIM-1) were significantly associated with the estimated risk for DKD. Raw path coefficients for cystatin C were 3.16 (95% CI 0.78; 5.53; p = 0.009, false discovery rate (FDR) < 5%), renal resistance index -8.14 (95% CI -15.36; -0.92; p = 0.027; FDR < 5%) and for KIM-1 0.47 (95% CI 0.02; 0.93; p = 0.040; FDR < 5%). Conclusion: Cystatin C, renal resistance index, and KIM-1 may be associated with the risk for DKD in children and adolescents diagnosed with DM-T1. We encourage further prospective cohort studies to test our results.